Coordinated control of multiple converters in model-free AC/DC distribution networks based on reinforcement learning - Zhao, Qianyu; Han, Zhaoyang; Wang, Shouxiang; Dong, Yichao; Qian, Guangchao (Frontiers in Energy Research, 2023)
Taking into account the challenges of obtaining accurate physical parameters and uncertainties arising from the integration of a large number of sources and loads, this paper proposes a real-time voltage control method for AC/DC distribution networks. The method utilizes model-free generation and coordinated control of multiple converters, and employs a combination of agent modeling and multi-agent soft actor critic (MASAC) techniques for modeling and solving the problem. Firstly, a complex nonlinear mapping relationship between bus power and voltage is established by training an power-voltage model, to address the issue of obtaining physical parameters in AC/DC distribution networks. Next, a Markov decision process is established for the voltage control problem, with multiple intelligent agents distributed to control the active and reactive power at each converter, in response to the uncertainties of PV and load variations. Using the MASAC method, a centralized training strategy and decentralized execution policy are implemented to achieve distributed control of the converters, with each converter making optimal decisions based on its local observation state. Finally, the proposed method is verified by numerical simulations, demonstrating its sound effectiveness and generalization ability.